FLY ASH NANOPARTICLES ASSITED FOAM INJECTION WATER ALTERNATING GAS FOR ENHANCED OIL RECOVERY - PHONG , GUAN MING (2021)
The success of foam injection as a displacing fluid in the porous media mainly depends on the stability of the foam. However, foam stability tends to decrease once exposed to crude oil and reservoir conditions. In the last few decades, research on nanoparticles as a foam stabilizer has shown favourable results, however, for field-scale application the nanoparticles for foam stabilization would have to be commercially feasible thus require an inexpensive alternative source that can be produced in large quantity. Coal fly ash is a by-product of burning coal for electricity in Malaysia, thus can serve as a source for low-cost large-scale production of nanoparticles. A chemical synthesis technique is used to synthesize nanoparticles from the coal fly ash as the technique is proven successful in producing much smaller nanoparticles capable of effective movement in the narrow lamellae space of the gas-liquid interface as compared to the larger-sized particles.